Research evolution in banking performance: a bibliometric analysis - Alam, S. M. Shamsul; Chowdhury, Mohammad Abdul Matin; Abdul Razak, Dzuljastri (Springer Open, 2021)
Banking performance has been regarded as a crucial factor of economic growth. Banks collect deposits from surplus and provide loans to the investors that contribute to the total economic growth. Recent development in the banking industry is channelling the funds and participating in economic activities directly. Hence, academic researchers are gradually showing their concern on banking performance and its efect on economic growth. Therefore, this study aims to explore the academic researchers on this particular academic research article. By extracting data from the web of Science online database, this study employed the bibliometrix package (biblioshiny) in the ‘R’ and VOSviewer tool to conduct performance and science mapping analyses. A total of 1308 research documents were analysed, and 36 documents were critically reviewed. The fndings exhibited a recent growth in academic publications. Three major themes are mainly identifed, efciency measurement, corporate governance efect and impact on economic growth. Besides, the content analysis represents the most common analysis techniques used in the past studies, namely DEA and GMM. The fndings of this study will be benefcial to both bank managers and owners to gauge a better understanding of banking performance. Meanwhile, academic researchers and students may fnd the fndings and suggestions to study in the banking area.